Effects of rTMS on swallowing function and neuroimaging features in post-stroke dysphagia - Chen, Xuting; Ma, Lianjie; Hou, Mengdi; Gu, Xudong; Wang, Zhongli; Yao, Yunhai; Fu, Jianming; Zhu, Meihong; Wang, Jie; Wang, Chaofan; Sun, Xiaolin; Zhang, Ting; et al. (Frontiers in Human Neuroscience, 2025)
IntroductionDysphagia, or difficulty swallowing, is common after stroke and can lead to complications like malnutrition, aspiration pneumonia, and increased mortality. Recovery is driven by neural reorganization, yet traditional interventions focus on managing swallowing difficulties rather than restoring brain function. Neuromodulatory approaches like repetitive transcranial magnetic stimulation (rTMS) show potential for promoting brain plasticity and recovery. While rTMS has demonstrated efficacy in improving swallowing after stroke, few studies have explored its neural mechanisms at the brain level, as opposed to focusing on motor-evoked potentials recorded from peripheral muscles.MethodsThis study examined the effects of 5 Hz rTMS on post-stroke dysphagia by targeting the contralesional mylohyoid cortical area. Resting-state fMRI was employed to investigate the neural correlates of rTMS effects. Local brain activity was measured using the amplitude of low-frequency fluctuation (ALFF), fractional amplitude of low-frequency fluctuation (fALFF), and percentage amplitude of fluctuation (PerAF), while network connectivity was assessed with graph theory analysis.ResultsrTMS reduced spontaneous activity in the contralesional middle frontal gyrus and putamen, and in the ipsilesional insula and middle frontal gyrus (pars orbitalis), regions that were hyperactive at baseline in dysphagic patients. Altered network topology in the left medial superior frontal gyrus suggested connectivity reorganization.ConclusionThese preliminary findings support rTMS as a promising adjunct therapy for post-stroke dysphagia by inducing cortical plasticity, as demonstrated by changes in both regional activity and network topology. Further validation in studies with larger samples is needed.